THE ROLE OF VISUAL GRAPHICS METHODS IN ENRICHING ENGLISH VOCABULARY: THE ROLE OF VISUAL GRAPHICS METHODS IN ENRICHING ENGLISH VOCABULARY - Adigamova, Roza; Utepbergenova, Damegul (Журнал иностранных языков и лингвистики, 2025)
Vocabulary is a cornerstone of language acquisition, serving as the basis for all four core skills: reading, writing, speaking, and listening. Without a strong vocabulary, learners struggle to express themselves effectively or comprehend authentic materials. As language learners face the challenge of mastering a vast number of English words and expressions, traditional approaches such as rote memorization often prove insufficient. The complexity of the English language—its irregular spelling, extensive synonymy, idiomatic use, and polysemy—further complicates the process. To overcome these obstacles, educators increasingly rely on visual graphics methods, which are grounded in cognitive learning theory and promote meaningful, engaging vocabulary acquisition.